2016
DOI: 10.1371/journal.pone.0167825
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabolome Analyses in Exogenous FABP4- and FABP5-Treated Adipose-Derived Stem Cells

Abstract: Adipose-derived stem cells (ADSC), which exist near adipocytes in adipose tissue, have been used as a potential tool of regenerative medicine. Lipid chaperones, fatty acid-binding protein 4 (FABP4) and 5 (FABP5), are abundantly expressed in adipocytes. FABP4 has recently been shown to be secreted from adipocytes during lipolysis in a non-classical pathway and may act as an adipokine. Here, we investigated the role of exogenous FABP4 and FABP5 in transcriptional and metabolic regulation in ADSC. FABP4 and FABP5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…To investigate whether cells present in the tumor microenvironment can influence metastatic TNBC cell behavior and expression of CYP2C19, FABP4, and FABP5, we used an in vitro co-culture model, selecting some of the representative tumor stromal cells, namely fibroblasts, adipocytes, and cells of monocytic lineage known to influence lipid homeostasis in breast cancer cells [8,[43][44][45][46]. Prior to co-culture with TNBC cells, first, we examined the adipogenic markers in undifferentiated fibroblasts (3T3-L1), a stable adipocyte differentiated cell line derived from 3T3-L1 (3T3-adipocytes); an undifferentiated monocytic cell line (THP-1), peroxisome proliferator-activated receptor-γ (PPAR-γ), which regulates adipocyte differentiation; CCAAT/enhancer binding protein α (C/EBPα) which is responsible for mitotic growth arrest and late-stage adipocyte differentiation; and FABP4, FABP5, and CYP2C19 in the THP-1 and 3T3-L1 cells.…”
Section: Potential Mechanistic Involvement Of Stromal Cells: Expressimentioning
confidence: 99%
“…To investigate whether cells present in the tumor microenvironment can influence metastatic TNBC cell behavior and expression of CYP2C19, FABP4, and FABP5, we used an in vitro co-culture model, selecting some of the representative tumor stromal cells, namely fibroblasts, adipocytes, and cells of monocytic lineage known to influence lipid homeostasis in breast cancer cells [8,[43][44][45][46]. Prior to co-culture with TNBC cells, first, we examined the adipogenic markers in undifferentiated fibroblasts (3T3-L1), a stable adipocyte differentiated cell line derived from 3T3-L1 (3T3-adipocytes); an undifferentiated monocytic cell line (THP-1), peroxisome proliferator-activated receptor-γ (PPAR-γ), which regulates adipocyte differentiation; CCAAT/enhancer binding protein α (C/EBPα) which is responsible for mitotic growth arrest and late-stage adipocyte differentiation; and FABP4, FABP5, and CYP2C19 in the THP-1 and 3T3-L1 cells.…”
Section: Potential Mechanistic Involvement Of Stromal Cells: Expressimentioning
confidence: 99%
“…The present results showed that daidzein significantly upregulated the expression level of FABP7 and ELOVL genes and significantly downregulated the expression level of GPR41 and SCD genes. FABP7 gene is a member of fatty acid-binding protein family and played an important role in the uptake of long-chain fatty acid in cytomembrane (Yamamoto et al, 2016). ELOVL gene could elongate the long-chain fatty acid in adipocytes (Harkewicz et al, 2012).…”
Section: Effects Of Daidzein On Triglyceride Synthesis In Subcutanementioning
confidence: 99%
“…It is reported that FABP4 is an adipokine with a distinct role of transcriptional and metabolic regulation in ASCs [45]. In this study, ORO staining results showed that both ASCs were induced when cultured in adipogenic medium and orbital ASCs have more adipogenic property compared to abdominal ASCs, which was ascertained by mRNA expressions of genes involved in adipogenesis.…”
Section: Discussionmentioning
confidence: 53%